DSi as a Tracer for Submarine Groundwater Discharge - Oehler, Till; Tamborski, Joseph; Rahman, Shaily; Moosdorf, Nils; Ahrens, Janis; Mori, Corinna; Neuholz, René; Schnetger, Bernhard; Beck, Melanie (Frontiers in Marine Science, 2019)
Submarine groundwater discharge (SGD) is an important source of nutrients and metals to the coastal ocean, affects coastal ecosystems, and is gaining recognition as a relevant water resource. SGD is usually quantified using geochemical tracers such as radon or radium. However, a few studies have also used dissolved silicon (DSi) as a tracer for SGD, as DSi is usually enriched in groundwater when compared to surface waters. In this study, we discuss the potential of DSi as a tracer in SGD studies based on a literature review and two case studies from contrasting environments. In the first case study, DSi is used to calculate SGD fluxes in a tropical volcanic-carbonate karstic region (southern Java, Indonesia), where SGD is dominated by terrestrial groundwater discharge. The second case study discusses DSi as a tracer for marine SGD (i.e. recirculated seawater) in the tidal flat area of Spiekeroog (southern North Sea), where SGD is dominantly driven by tidal pumping through beach sands. Our results indicate that DSi is a useful tracer for SGD in various lithologies (e.g. karstic, volcanic, complex) to quantify terrestrial and marine SGD fluxes. DSi can also be used to trace groundwater transport processes in the sediment and the coastal aquifer. Care has to be taken that all sources and sinks of DSi are known and can be quantified or neglected. One major limitation is that DSi is used by siliceous phytoplankton and therefore limits its applicability to times of the year when primary production of siliceous phytoplankton is low. In general, DSi is a powerful tracer for SGD in many environments. We recommend that DSi should be used to complement other conventionally used tracers, such as radon or radium, to help account for their own shortcomings.